Intensive simulation versus control in the assessment of time to skill competency and confidence of medical students to assess and manage cardiovascular and respiratory conditions—a pseudo-randomised trial. Issue 1 (January 2016) - Cunningham, Neil; O'Brien, Robert; Weiland, Tracey; van Dijk, Julian; Dilley, Stuart
Abstract Background The Clinical Placement Enhancement Program (CPEP) is a simulation course for medical students learning the core topics of cardiovascular and respiratory medicine, incorporating patient safety and professionalism teaching and based on adult learning principles and proven educational theory. The aims of this study are to assess whether the CPEP delivered at the beginning of a clinical rotation would result in competency outcomes that are at least equivalent to those achieved through a standard 6-week programme and whether this programme would increase student confidence levels in assessing and managing patients with cardiovascular and respiratory conditions. Methods This was a pseudo-randomised control trial between two groups of medical students from one clinical school. The intervention group participated in CPEP, a 4-day immersive simulation course, in the first week of their cardiac and respiratory medicine clinical rotation. The control group participants attended the normal programme of the 6-week cardiovascular and respiratory medicine clinical rotation. The programme and student competence was assessed using Observed Structured Clinical Examinations (OSCEs) and self-reported confidence surveys. Results There was no significant difference in OSCE scoring between the intervention group (examined in week one of their clinical rotation following CPEP) and the control group (examined at the end of their full clinical rotation). Students exposed to CPEP started their clinical rotation with confidence levels similar to those reported by the control group at the end of their rotation. Confidence levels of CPEP students were higher at the end of the rotation compared to those of the control group. Conclusions Based on OSCE results, immersion into a 4-day simulation-based teaching programme at the start of a clinical rotation resulted in skill competency levels that were equivalent to those obtained after a full clinical rotation of 6 weeks. CPEP improved students' confidence levels in the assessment and management of patients presenting with cardiovascular and respiratory conditions. Simulation utilised in courses such as CPEP has the potential to enhance the overall learning experience in medical school clinical rotations.